International linkages among stock markets of Malaysia and its major trading partners - Karim, Bakri Abdul; Majid, M. Shabri ABD. (Taylor ans Francis, 2009)
This study empirically examines the short- and long-run dynamic causal linkages between Malaysia and its major trading partners (the United States, Japan, Singapore, China, and Thailand) based on a two-step estimation, Autoregressive distributed lag (ARDL) and Generalized Method of Moments (GMM) during the period 1992–2008. The study documents that the stronger the trade ties among the countries, the higher the degree of comovements among their stock markets. The Japanese stock market, to some extent, is found to be more important than the United States over these markets. In designing stock market policies, each country should take into consideration of any shocks in its major trading partners.